ISOLASI ALFA SELULOSA DAN PEMBUATAN SERTA KARAKTERISASI MIKROKRISTALIN SELULOSA DARI KULIT BUAH LIMPASU (Baccaurea lanceolata Muell) - Yuspa, Yuspa; Hafifah, Rahmalisa; Mursyidah, Siti; aldeina, Soraya; Muhammad, Muhammad; Indah Lestari, Yulianita Pratiwi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Indonesia is rich in biological natural resources and has diversity spread throughout Indonesia. One of the typical Indonesian plants, especially in Kalimantan, is Limpasu. Limpasu is a typical Kalimantan plant, where this plant has many nutritious contents such as antioxidants and has high potential to be used as a raw material for making microcrystalline cellulose. Microcrystalline Cellulose (MCC) is cellulose that is partially purified, then processed with ɑ-cellulose preparations. The aim of this research is to obtain microcrystalline cellulose from Limpasu fruit peel waste. The research method used in this research is chemical delignification, followed by hydrolysis using dilute acid to produce MCC, then characterized with Avicel PH 102 as a commercial comparison. Based on the research results, the yield of α-cellulose was 14.14% for simplicia powder, the MCC yield was 11.48% for α-cellulose and the characterization of MCCKBL powder showed similar characteristics to Avicel® PH 102 as a comparison.